2020
DOI: 10.7150/thno.45488
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in Inflammatory Skin Disorders: from Pathophysiology to Treatment

Abstract: Extracellular vesicles (EVs), naturally secreted by almost all known cell types into extracellular space, can transfer their bioactive cargos of nucleic acids and proteins to recipient cells, mediating cell-cell communication. Thus, they participate in many pathogenic processes including immune regulation, cell proliferation and differentiation, cell death, angiogenesis, among others. Cumulative evidence has shown the important regulatory effects of EVs on the initiation and progression of inflammation, autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 254 publications
(263 reference statements)
0
44
0
1
Order By: Relevance
“…Identification of neutrophil-derived exosomes as a new subcellular entity could result in elucidation of a molecular player providing a fundamental link between neutrophil-driven inflammation and multi-organ tissue damage observed in ENL with far-reaching implications for future research. Neutrophil-derived exosomes have already been demonstrated as a new means of intercellular communication promoting extracellular matrix destruction in an array of chronic inflammatory lung disease and have key immunomodulatory roles in a variety of inflammatory dermatological disorders, justifying their role as biomarkers indicating a variety of pathophysiological states ( 109 111 ).…”
Section: Neutrophil Biologymentioning
confidence: 99%
“…Identification of neutrophil-derived exosomes as a new subcellular entity could result in elucidation of a molecular player providing a fundamental link between neutrophil-driven inflammation and multi-organ tissue damage observed in ENL with far-reaching implications for future research. Neutrophil-derived exosomes have already been demonstrated as a new means of intercellular communication promoting extracellular matrix destruction in an array of chronic inflammatory lung disease and have key immunomodulatory roles in a variety of inflammatory dermatological disorders, justifying their role as biomarkers indicating a variety of pathophysiological states ( 109 111 ).…”
Section: Neutrophil Biologymentioning
confidence: 99%
“…Another recent study has shown the involvement of EVs in dermatitis. It was observed that EV-associated α-Hemolysin secreted by S. aureus induced keratinocyte death, skin barrier disruption and inflammation (release IL-1β, IL-6, IL-8, and MIP-1α)—the key phenotypes associated with atopic dermatitis (AD) [ 172 , 173 , 174 ]. Additionally, it was found that there was an increase in the pro-inflammatory mediators, including IL-6, thymic stromal lymphopoietin (TSLP), MIP-1α, and eotaxin, in mouse dermal fibroblasts cells exposed to S. aureus EVs [ 175 ].…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
“…Abnormal microangiogenesis is closely related to the development of psoriasis (33). Microcirculation disturbances and hemorheological changes are observed in the skin lesions of psoriatic patients (34). In this study, we found that PSORI-CM02 inhibited the proliferation and migration of IL-17Astimulated HUVECs and reduced new blood vessel growth in the skin of mice with IMQ-induced psoriasis.…”
Section: Discussionmentioning
confidence: 51%